Effect of using normal saline, alcohol and acetone on pain during removal of polyacrylate adhesive dressings in children aged 10–15 years: a pilot randomized controlled trial - Edith Sumaregita Rinhastyanti; Herman Wihastyoko; Tommy Alfandy Nazwar (Faculty of Medicine, Universitas Trisakti, 2026)
BackgroundRemoving wound dressings containing polyacrylate adhesives can cause pain, especially in pediatric patients with more sensitive skin and lower pain thresholds. This study aimed to evaluate the effects of normal saline, alcohol, and acetone on pain during dressing removal in children and evaluate their associated side effects. MethodsThe study used a pilot randomized controlled trial involving 16 children aged 10-15 years at the Surgical Clinic of Dr. Saiful Anwar Regional General Hospital, Malang. Pain levels were measured using the Wong-Baker Faces Pain Scale, while side effects were assessed using the Skin Irritation Score and Itchyquant Score. The children's pain was assessed 1 min after the procedure. Kruskal-Wallis test, followed by Dunn's post hoc test were used for data analysis. ResultsThe results demonstrated that acetone was significantly more effective than normal saline and alcohol in reducing pain during dressing removal (p<0.050). Normal saline and alcohol did not show significant differences compared to the control group, likely due to their limited ability to dissolve the polyacrylate adhesive. Mild irritation and temporary pruritus occurred in all groups, with acetone producing the least reaction. Acetone's effectiveness is attributed to its ability to disrupt van der Waals forces and polymer bonds within the adhesive, thereby reducing the force required for removal. ConclusionsAcetone is the most effective agent for reducing pain during dressing removal, with minimal side effects compared to other solvents. Further research is necessary to determine optimal formulations and assess the stability of acetone for the development of acetone swab products.